Preparation method of warm-keeping breathable fiber

By forming a cross-linked interpenetrating network on the fiber, the problem of poor fixation effect of phase change materials in the fiber is solved, and the water washing resistance and moisture permeability of the fiber are significantly improved.

CN119615613AActive Publication Date: 2025-03-14JIANGSU HENGLI CHEM FIBER
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510149118.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-03-14
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

In the prior art, the phase change material has poor fixation effect in the fiber, resulting in low washing resistance.

Method used

By soaking flax fibers or cellulose fibers in aqueous glutaraldehyde solution, then treating them in molten polyethylene glycol, and adding metal ions to the aqueous polyphenol solution for self-assembly, and finally cross-linking reactions are carried out in aqueous glutaraldehyde solution to form a cross-linking interpenetration network, thereby improving the fixation effect of phase change materials.

Benefits of technology

The phase change material is achieved firmer fixation on the fiber, improving the water-washing resistance and moisture permeability of the fiber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615613A_ABST
    Figure CN119615613A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of warm-keeping breathable fibers, and discloses a preparation method of warm-keeping breathable fibers, which comprises the following steps: soaking linen fibers or cellulosic fibers in a glutaraldehyde aqueous solution I to obtain a product I, then taking out the product I, soaking the product I in polyethylene glycol in a molten state to obtain a product II, and drying the product II to obtain the warm-keeping breathable fibers. Then the product II is taken out and soaked in a polyphenol aqueous solution, a metal ion aqueous solution is added into the polyphenol aqueous solution, self-assembly of a metal polyphenol network is carried out, a product III is obtained, the metal polyphenol network is obtained through coordination of metal ions and polyphenol, finally, the product III is taken out and soaked in a glutaraldehyde aqueous solution II for a reaction, and the final product is obtained. The fibers are warm-keeping breathable fibers; wherein in the solution obtained after the metal ion aqueous solution is added into the polyphenol aqueous solution, the molar weight of metal ions is larger than that of polyphenol. According to the invention, a cross-linked interpenetrating network is formed through a plurality of cross-links, so that the solid-phase material polyethylene glycol is fixed more firmly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal insulation and breathable fibers, and relates to a method for preparing the thermal insulation and breathable fibers. Background Art

[0002] Flax fiber or cellulose fiber has excellent comfort. In summer, flax fiber or cellulose fiber absorbs and releases moisture quickly, which can effectively adjust the ecological temperature environment of the human skin surface and has good air permeability. Phase change materials can change their own phases according to changes in ambient temperature, store heat or release heat. In winter, flax fiber or cellulose fiber can be used in combination with phase change materials to achieve sufficient warmth retention. However, the content of phase change materials added to fibers is often low and unstable, and there is a high possibility of overflowing from the fibers, so they need to be effectively fixed.

[0003] For example, the literature (Preparation of PAN / phase change microcapsule composite phase change fiber by wet spinning and its performance research [J]. Synthetic Fiber Industry, 2024, 47 (4): 1.) prepared spinning solution by blending polyurea-coated n-octadecane phase change microcapsules (MPCM) with polyacrylonitrile (PAN), and prepared PAN / MPCM composite phase change fibers with different MPCM contents by wet spinning. However, in practical applications, the shell material of low-content phase change microcapsules will leak due to physical damage or chemical degradation, resulting in low water wash resistance.

[0004] On this basis, patent CN118127653A discloses a regenerated natural polymer-based solid-solid phase change fiber and its preparation method and application. The technical solution is to use natural polymer materials as raw materials, graft with single functional group phase change materials to obtain natural polymer-based solid-solid phase change materials, and use solution spinning to obtain regenerated natural polymer-based solid-solid phase change fibers. However, the fiber prepared by this method has a low degree of cross-linking, and the cross-linking structure is easily destroyed, resulting in the inability of the phase change material to be densely encapsulated in the fiber, and the water washing performance is low.

[0005] Therefore, it is of great significance to study a method for preparing a thermal-insulating and breathable fiber to improve the fixation effect of phase change materials on the fiber. Summary of the invention

[0006] The purpose of the present invention is to solve the problems existing in the prior art and provide a method for preparing a thermal insulation and breathable fiber.

[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a thermal insulation breathable fiber comprises: soaking flax fiber or cellulose fiber in a glutaraldehyde aqueous solution I to obtain a product I, then taking out the product I and soaking it in polyethylene glycol in a molten state to obtain a product II, then taking out the product II and soaking it in a polyphenol aqueous solution, adding a metal ion aqueous solution to the polyphenol aqueous solution to self-assemble a metal polyphenol network on the polyethylene glycol to obtain a product III, and finally taking out the product III and soaking it in a glutaraldehyde aqueous solution II to react to obtain a final product, namely the thermal insulation breathable fiber;

[0009] The metal polyphenol network is obtained by the coordination of metal ions and polyphenols;

[0010] In the solution obtained after adding the aqueous solution of metal ions to the aqueous solution of polyphenols, the molar amount of the metal ions is greater than the molar amount of the polyphenols;

[0011] The preparation process involves a variety of cross-linked structures. In the following, PEG represents polyethylene glycol, M represents metal ions, P represents polyphenol, -OH represents hydroxyl, and GA represents glutaraldehyde. When flax fiber or cellulose fiber is immersed in glutaraldehyde aqueous solution I, since flax fiber or cellulose fiber has hydroxyl groups, the glutaraldehyde in glutaraldehyde aqueous solution I reacts with the hydroxyl groups on flax fiber or cellulose. After that, after being placed in polyethylene glycol in a molten state, another aldehyde group of glutaraldehyde reacts with the hydroxyl groups on polyethylene glycol to form a cross-linked structure O-GA-O; after adding a metal ion aqueous solution to the polyphenol aqueous solution, some metal ions coordinate with the hydroxyl groups in the polyphenol to form a metal polyphenol network outside the polyethylene glycol layer, and some metal ions coordinate with the hydroxyl groups in the polyethylene glycol to form a cross-linked structure PEG-MP; after being placed in a glutaraldehyde aqueous solution II, the glutaraldehyde in the glutaraldehyde aqueous solution II will react with the remaining reactive hydroxyl groups in PEG-MP to form ; The glutaraldehyde in the glutaraldehyde aqueous solution II also reacts with polyethylene glycol and polyphenol that have not undergone cross-linking reaction to obtain a cross-linked structure PEG-GA-P; the above-mentioned various cross-linked structures interpenetrate each other to form a cross-linked interpenetrating network, thereby making the solid phase material polyethylene glycol more firmly fixed;

[0012] In addition, it should be noted that the polyethylene glycol in the molten state in the present invention is more easily physically adsorbed onto the flax fiber or the cellulose fiber than the solid polyethylene glycol or the liquid polyethylene glycol.

[0013] As the preferred technical solution:

[0014] The preparation method of the above-mentioned thermal insulation and breathable fiber comprises the following specific preparation steps:

[0015] (1) Soaking flax fiber or cellulose fiber in a 30-50 wt% glutaraldehyde aqueous solution I for 6-24 hours; the temperature of the glutaraldehyde aqueous solution I is 25-45° C.;

[0016] (2) placing the product soaked in step (1) in molten polyethylene glycol for 0.5 to 2 hours, and then vacuum drying at 40 to 60° C. for 4 to 8 hours;

[0017] (3) placing the vacuum-dried product of step (2) in a polyphenol aqueous solution with a concentration of 1 to 10 wt% for 10 to 30 minutes, then pouring a 10 to 25° C. metal ion aqueous solution into the polyphenol aqueous solution and allowing to stand for 2 to 8 hours, and finally drying the product at 25 to 60° C. for 20 to 40 minutes;

[0018] (4) The dried product of step (3) is placed in a 10-30wt% glutaraldehyde aqueous solution II for 6-24 hours, and then the soaked fiber is taken out, and excess glutaraldehyde in the glutaraldehyde aqueous solution II is removed with water, and then dried at room temperature for 24-72 hours to obtain a thermal insulation and breathable fiber.

[0019] In the method for preparing a thermal breathable fiber as described above, the mass volume ratio of flax fiber or cellulose fiber to glutaraldehyde aqueous solution I is 1:10-50.

[0020] In the method for preparing a thermal and breathable fiber as described above, the mass volume ratio of the product after immersion in step (1) to the molten polyethylene glycol is 1:10-30; the mass volume ratio of the product after vacuum drying in step (2) to the polyphenol aqueous solution is 1:5-25; and the mass volume ratio of the product after drying in step (3) to the glutaraldehyde aqueous solution II is 1:4-20.

[0021] In the method for preparing a thermal breathable fiber as described above, the molar ratio of polyphenols to metal ions is 1:2-10.

[0022] In the preparation method of a thermal and breathable fiber as described above, the metal ions are one or more of copper ions, zinc ions, zirconium ions, iron ions and ferrous ions; the polyphenols are one or more of tannic acid, gallic acid, catechol and pyrogallol; and the polyethylene glycol is one or more of polyethylene glycol 1000, polyethylene glycol 2000, polyethylene glycol 4000, polyethylene glycol 6000 and polyethylene glycol 10000.

[0023] The method for preparing a thermal-insulating breathable fiber as described above, wherein the moisture permeability of the cloth made of the thermal-insulating breathable fiber at 20°C is 6174~6278g·(m 2 24h) -1 The change rate of moisture permeability after washing at 20℃ is 1.3~3.7%, and the moisture permeability at 30℃ is 7492~7597g·(m 2 24h) -1The change rate of moisture permeability after washing at 30℃ is 1.7~3%, and the moisture permeability at 40℃ is 8795~8906g·(m 2 24h) -1 The change rate of moisture permeability after washing at 40°C is 1.9~3%.

[0024] Beneficial effects:

[0025] The present invention forms a cross-linked interpenetrating network by interpenetrating a plurality of cross-linked structures, thereby making the solid phase material polyethylene glycol more firmly fixed; in addition, the present invention limits the polyethylene glycol to a molten state, which can make it easier to physically adsorb onto flax fibers or cellulose fibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the UV-visible absorption spectrum of product II in Example 3 of the present invention;

[0027] Figure 2 This is the UV-visible absorption spectrum of the thermal-retaining breathable fiber prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0029] In order to ensure that the properties of the materials used in each embodiment and comparative example are fully disclosed, the manufacturers and brands of the materials are indicated, and products of other manufacturers and brands that meet the requirements of the present invention are also feasible.

[0030] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:

[0031] The test method of moisture permeability and moisture permeability change rate after washing, the specific steps are as follows:

[0032] (1) The thermal insulation and breathable fibers prepared in each embodiment are first combed into single fibers (single fibers), and then 50 single fibers are combined to form a continuous fiber strip, and finally the fiber strip is stretched and twisted to form a spun yarn; wherein the stretching temperature is 40°C, the stretching elongation is 30%, the stretching rate is 1 mm / min, and the twist is 20 twists / m;

[0033] (2) using a shuttle loom, the spun yarn prepared in step (1) is used as warp yarn and weft yarn to weave a cloth having a thickness of 1 mm;

[0034] (3) The moisture permeability of the prepared fabric was tested at 20°C, 30°C and 40°C respectively according to GB / T 12704.1-2009 "Test method for moisture permeability of textile fabrics - Part 1: Moisture absorption method"; then the fabric was washed 40 times according to GB / T 8629-2017 "Household washing and drying procedures for testing textiles" (test conditions: using type A washing machine, washing procedure 1 and standard detergent 2), and finally the washed fabric was dried and made into a sample with a radius of 35 mm, and then the moisture permeability of the sample was tested according to GB / T12704.1-2009 "Test method for moisture permeability of textile fabrics - Part 1: Moisture absorption method"; then the moisture permeability change rate was calculated based on the moisture permeability of the fabric before and after washing.

[0035] When there are multiple solutes in the polyphenol aqueous solution and the metal ion aqueous solution, the molar ratio of polyphenol to metal ion refers to the ratio of the sum of the molar amounts of all solutes in the polyphenol aqueous solution to the sum of the molar amounts of all solutes in the metal ion aqueous solution.

[0036] Example 1

[0037] A method for preparing a thermal-retaining breathable fiber, comprising the following steps:

[0038] (1) immersing flax fiber (wet-spun flax yarn, manufactured by Jinda Holdings Limited, specification 75 NM) in a 30 wt % glutaraldehyde aqueous solution I for 6 h to obtain product I; wherein the temperature of the glutaraldehyde aqueous solution I is 25° C., and the mass volume ratio of the flax fiber to the glutaraldehyde aqueous solution I is 1:10;

[0039] (2) placing the product I obtained in step (1) in molten polyethylene glycol for 0.5 h, and then vacuum drying at 60° C. for 8 h to obtain product II; wherein the polyethylene glycol is composed of polyethylene glycol 1000 (manufacturer: Sinopharm Chemical Reagent Co., Ltd., specification: CP (Shanghai trial)) and polyethylene glycol 2000 (manufacturer: Sinopharm Chemical Reagent Co., Ltd., specification: CP (Shanghai trial)) in a mass ratio of 1:1, and the mass volume ratio of product I to molten polyethylene glycol is 1:10;

[0040] (3) dissolving cupric chloride dihydrate and ferric chloride hexahydrate in deionized water at 25° C. and mixing them evenly to obtain a 0.1 wt % aqueous solution of copper ions and iron ions; wherein the mass ratio of cupric chloride dihydrate to ferric chloride hexahydrate is 2:1;

[0041] (4) placing the product II obtained in step (2) in a 1 wt% gallic acid aqueous solution for 30 min, then pouring the 10° C. copper ion and iron ion aqueous solution obtained in step (3) into the gallic acid aqueous solution and keeping the temperature at room temperature for 2 h, and finally drying the product after standing at 25° C. for 20 min to obtain product III; wherein the mass volume ratio of product II to the gallic acid aqueous solution is 1:5, and the ratio of the molar amount of gallic acid to the sum of the molar amounts of copper ions and iron ions is 1:2;

[0042] (5) The product III obtained in step (4) is placed in a 30 wt% glutaraldehyde aqueous solution II for 6 hours, and then the product III is taken out after soaking, and the excess glutaraldehyde in the glutaraldehyde aqueous solution II is removed by water, and then dried at 25° C. for 24 hours to obtain a thermal insulation and breathable fiber; wherein the mass volume ratio of the product III to the glutaraldehyde aqueous solution II is 1:20.

[0043] The moisture permeability of the cloth made of the above-prepared warm breathable fiber at 20°C is 6278g·(m 2 24h) -1 The moisture permeability of the cloth after washing at 20°C changed by 1.8%, and the moisture permeability at 30°C was 7583 g·(m 2 24h) -1 The moisture permeability of the cloth after washing at 30°C changed by 2.3%, and the moisture permeability at 40°C was 8906 g·(m 2 24h) -1 The change rate of moisture permeability of the cloth after washing at 40°C is 2.8%.

[0044] Example 2

[0045] A method for preparing a thermal-retaining breathable fiber, comprising the following steps:

[0046] (1) immersing flax fiber (wet-spun flax yarn, manufactured by Jinda Holdings Co., Ltd., specification 75 NM) in a glutaraldehyde aqueous solution I with a concentration of 40 wt % for 15 h to obtain a product I; wherein the temperature of the glutaraldehyde aqueous solution I is 35° C., and the mass volume ratio of the flax fiber to the glutaraldehyde aqueous solution I is 1:30;

[0047] (2) placing the product I obtained in step (1) in molten polyethylene glycol for 1.2 hours, and then vacuum drying at 50°C for 6 hours to obtain product II; wherein the polyethylene glycol is composed of polyethylene glycol 4000 (manufacturer: Sinopharm Chemical Reagent Co., Ltd., specification: CP (Shanghai trial)) and polyethylene glycol 10000 (manufacturer: Sinopharm Chemical Reagent Co., Ltd., specification: CP (Shanghai trial)) in a mass ratio of 3:2, and the mass volume ratio of product I to molten polyethylene glycol is 1:20;

[0048] (3) dissolving zinc chloride tetrahydrate and zirconium oxychloride octahydrate in deionized water at 25° C. and mixing them evenly to obtain an aqueous solution of zinc ions and zirconium ions with a concentration of 2 wt %; wherein the mass ratio of zinc chloride tetrahydrate to zirconium oxychloride octahydrate is 1:2;

[0049] (4) placing the product II obtained in step (2) in a 10 wt % aqueous solution of catechol and pyrogallol for 20 min, then pouring the 18° C. aqueous solution of zinc ions and zirconium ions obtained in step (3) into the aqueous solution of catechol and pyrogallol and keeping the temperature for 5 h, and finally drying the product after standing at 60° C. for 30 min to obtain product III; wherein the mass ratio of catechol to pyrogallol in the aqueous solution of catechol and pyrogallol is 1:4, the mass volume ratio of product II to the aqueous solution of catechol and pyrogallol is 1:25, and the ratio of the sum of the molar amounts of catechol and pyrogallol to the sum of the molar amounts of zinc ions and zirconium ions is 1:10;

[0050] (5) The product III obtained in step (4) is placed in a 10 wt% glutaraldehyde aqueous solution II for 15 h, and then the product III is taken out after soaking, and the excess glutaraldehyde in the glutaraldehyde aqueous solution II is removed by water, and then dried at 25 ° C for 48 h to obtain a thermal insulation and breathable fiber; wherein the mass volume ratio of the product III to the glutaraldehyde aqueous solution II is 1:12.

[0051] The moisture permeability of the cloth made of the above-prepared warm breathable fiber at 20°C is 6265g·(m 2 24h) -1 The moisture permeability of the cloth after washing at 20°C changes by 3.7%, and the moisture permeability at 30°C is 7595 g·(m 2 24h) -1 The moisture permeability of the cloth after washing at 30°C changed by 2.7%, and the moisture permeability at 40°C was 8911 g·(m 2 24h) -1 , the change rate of moisture permeability of the cloth after washing at 40°C is 3%.

[0052] Example 3

[0053] A method for preparing a thermal-retaining breathable fiber, comprising the following steps:

[0054] (1) immersing flax fiber (wet-spun flax yarn, manufactured by Jinda Holdings Limited, specification 75 NM) in a glutaraldehyde aqueous solution I with a concentration of 50 wt % for 24 h to obtain a product I; wherein the temperature of the glutaraldehyde aqueous solution I is 45° C., and the mass volume ratio of the flax fiber to the glutaraldehyde aqueous solution I is 1:50;

[0055] (2) placing the product I obtained in step (1) in molten polyethylene glycol 6000 (manufacturer: Sinopharm Chemical Reagent Co., Ltd., specification: CP (Shanghai test)) for 2 h, and then vacuum drying at 40°C for 4 h to obtain product II; wherein the mass volume ratio of product I to molten polyethylene glycol is 1:30;

[0056] (3) dissolving ferrous chloride tetrahydrate in deionized water at 25° C. and mixing well to obtain a 0.5 wt % ferrous ion aqueous solution;

[0057] (4) placing the product II obtained in step (2) in a 6 wt % tannic acid aqueous solution for 10 min, then pouring the 25° C. ferrous ion aqueous solution obtained in step (3) into the tannic acid aqueous solution and keeping the temperature at that for 8 h, and finally drying the product after standing at 40° C. for 40 min to obtain product III; wherein the mass volume ratio of product II to the tannic acid aqueous solution is 1:15, and the molar ratio of tannic acid to ferrous ion is 1:5;

[0058] (5) The product III obtained in step (4) is placed in a 20 wt% glutaraldehyde aqueous solution II for 24 hours, and then the product III is taken out after soaking, and the excess glutaraldehyde in the glutaraldehyde aqueous solution II is removed by water, and then dried at 25° C. for 72 hours to obtain a thermal insulation and breathable fiber; wherein the mass volume ratio of the product III to the glutaraldehyde aqueous solution II is 1:4.

[0059] The product II and the thermal breathable fiber prepared in this embodiment were washed in ultrapure water for 10 times, 20 times, and 40 times, respectively, and then the washed solutions were tested for UV-visible absorption spectra. Figure 1 , Figure 2 As shown in the figure, it can be seen that the peak intensity of Product II increases significantly with the increase in the number of water washings, indicating that its coating is unstable and the cross-linked structure is easily destroyed, while the peak intensity of the thermal breathable fiber does not change basically with the increase in the number of water washings. Compared with Product II, the thermal breathable fiber has a higher degree of cross-linking and is not easily destroyed, making it more difficult for the solid phase material to separate from the flax fiber.

[0060] The moisture permeability of the cloth made of the above-prepared warm breathable fiber at 20°C is 6271g·(m 2 24h) -1 The moisture permeability of the cloth after washing at 20°C changes by 1.3%, and the moisture permeability at 30°C is 7597 g·(m 2 24h) -1 The moisture permeability of the cloth after washing at 30°C changed by 1.7%, and the moisture permeability at 40°C was 8885 g·(m 2 24h) -1The change rate of moisture permeability of the cloth after washing at 40°C is 1.9%.

[0061] Example 4

[0062] A method for preparing a thermal-retaining breathable fiber, comprising the following steps:

[0063] (1) Soaking cellulose fibers (manufacturer: Sateri Holdings Limited, brand: EcoCosy, model: BVF) in a 30 wt% glutaraldehyde aqueous solution I for 6 h to obtain product I; wherein the temperature of the glutaraldehyde aqueous solution I is 25° C., and the mass volume ratio of cellulose fibers to the glutaraldehyde aqueous solution I is 1:10;

[0064] (2) placing the product I obtained in step (1) in molten polyethylene glycol for 0.5 h, and then vacuum drying at 60° C. for 8 h to obtain product II; wherein the polyethylene glycol is composed of polyethylene glycol 1000 and polyethylene glycol 2000 (manufacturer: Sinopharm Chemical Reagent Co., Ltd., specification: CP (Shanghai test)) in a mass ratio of 1:1, and the mass volume ratio of product I to molten polyethylene glycol is 1:10;

[0065] (3) dissolving cupric chloride dihydrate and ferric chloride hexahydrate in deionized water at 25° C. and mixing them evenly to obtain a 0.1 wt % aqueous solution of copper ions and iron ions; wherein the mass ratio of cupric chloride dihydrate to ferric chloride hexahydrate is 2:1;

[0066] (4) placing the product II obtained in step (2) in a 1 wt% gallic acid aqueous solution for 30 min, then pouring the 10° C. copper ion and iron ion aqueous solution obtained in step (3) into the gallic acid aqueous solution and keeping the temperature at room temperature for 2 h, and finally drying the product after standing at 25° C. for 20 min to obtain product III; wherein the mass volume ratio of product II to the gallic acid aqueous solution is 1:5, and the ratio of the molar amount of gallic acid to the sum of the molar amounts of copper ions and iron ions is 1:2;

[0067] (5) The product III obtained in step (4) is placed in a 30 wt% glutaraldehyde aqueous solution II for 6 hours, and then the product III is taken out after soaking, and the excess glutaraldehyde in the glutaraldehyde aqueous solution II is removed by water, and then dried at 25° C. for 24 hours to obtain a thermal insulation and breathable fiber; wherein the mass volume ratio of the product III to the glutaraldehyde aqueous solution II is 1:20.

[0068] The moisture permeability of the cloth made of the above-prepared warm breathable fiber at 20°C is 6129g·(m 2 24h) -1 The moisture permeability of the cloth after washing at 20°C changed by 2.2%, and the moisture permeability at 30°C was 7492 g·(m2 24h) -1 The moisture permeability of the cloth after washing at 30°C is 3%, and the moisture permeability at 40°C is 8795g·(m 2 24h) -1 The change rate of moisture permeability of the cloth after washing at 40°C is 2.9%.

[0069] Example 5

[0070] A method for preparing a thermal-retaining breathable fiber, comprising the following steps:

[0071] (1) Soaking cellulose fibers (manufacturer: Sateri Holdings Limited, brand: EcoCosy, model: BVF) in a glutaraldehyde aqueous solution I with a concentration of 40 wt% for 15 h to obtain a product I; wherein the temperature of the glutaraldehyde aqueous solution I is 35° C., and the mass volume ratio of the cellulose fibers to the glutaraldehyde aqueous solution I is 1:30;

[0072] (2) placing the product I obtained in step (1) in molten polyethylene glycol for 1.2 h, and then vacuum drying at 50° C. for 6 h to obtain product II; wherein the polyethylene glycol is composed of polyethylene glycol 4000 and polyethylene glycol 10000 in a mass ratio of 3:2 (manufacturer: Sinopharm Chemical Reagent Co., Ltd., specification: CP (Shanghai test)), and the mass volume ratio of product I to molten polyethylene glycol is 1:20;

[0073] (3) dissolving zinc chloride tetrahydrate and zirconium oxychloride octahydrate in deionized water at 25° C. and mixing them evenly to obtain an aqueous solution of zinc ions and zirconium ions with a concentration of 2 wt %; wherein the mass ratio of zinc chloride tetrahydrate to zirconium oxychloride octahydrate is 1:2;

[0074] (4) placing the product II obtained in step (2) in a 10 wt % aqueous solution of catechol and pyrogallol for 20 min, then pouring the 18° C. aqueous solution of zinc ions and zirconium ions obtained in step (3) into the aqueous solution of catechol and pyrogallol and keeping the temperature for 5 h, and finally drying the product after standing at 60° C. for 30 min to obtain product III; wherein the mass ratio of catechol to pyrogallol in the aqueous solution of catechol and pyrogallol is 1:4, the mass volume ratio of product II to the aqueous solution of catechol and pyrogallol is 1:25, and the ratio of the sum of the molar amounts of catechol and pyrogallol to the sum of the molar amounts of zinc ions and zirconium ions is 1:10;

[0075] (5) The product III obtained in step (4) is placed in a 10 wt% glutaraldehyde aqueous solution II for 15 h, and then the product III is taken out after soaking, and the excess glutaraldehyde in the glutaraldehyde aqueous solution II is removed by water, and then dried at 25 ° C for 48 h to obtain a thermal insulation and breathable fiber; wherein the mass volume ratio of the product III to the glutaraldehyde aqueous solution II is 1:12.

[0076] The moisture permeability of the cloth made of the above-prepared warm breathable fiber at 20°C is 6174g·(m 2 24h) -1 The moisture permeability of the cloth after washing at 20°C changed by 2.3%, and the moisture permeability at 30°C was 7524 g·(m 2 24h) -1 The moisture permeability of the cloth after washing at 30°C was 2.1%, and the moisture permeability at 40°C was 8804 g·(m 2 24h) -1 The change rate of moisture permeability of the cloth after washing at 40°C is 2.8%.

[0077] Example 6

[0078] A method for preparing a thermal-retaining breathable fiber, comprising the following steps:

[0079] (1) Soaking cellulose fibers (manufacturer: Sateri Holdings Limited, brand: EcoCosy, model: BVF) in a glutaraldehyde aqueous solution I with a concentration of 50 wt% for 24 h to obtain a product I; wherein the temperature of the glutaraldehyde aqueous solution I is 45° C., and the mass volume ratio of the cellulose fibers to the glutaraldehyde aqueous solution I is 1:50;

[0080] (2) placing the product I obtained in step (1) in molten polyethylene glycol 6000 (manufacturer: Sinopharm Chemical Reagent Co., Ltd., specification: CP (Shanghai test)) for 2 h, and then vacuum drying at 40°C for 4 h to obtain product II; wherein the mass volume ratio of product I to molten polyethylene glycol is 1:30;

[0081] (3) dissolving ferrous chloride tetrahydrate in deionized water at 25° C. and mixing well to obtain a 0.5 wt % ferrous ion aqueous solution;

[0082] (4) placing the product II obtained in step (2) in a 6 wt % tannic acid aqueous solution for 10 min, then pouring the 25° C. ferrous ion aqueous solution obtained in step (3) into the tannic acid aqueous solution and keeping the temperature at that for 8 h, and finally drying the product after standing at 40° C. for 20 min to obtain product III; wherein the mass volume ratio of product II to the tannic acid aqueous solution is 1:15, and the molar ratio of tannic acid to ferrous ion is 1:5;

[0083] (5) The product III obtained in step (4) is placed in a 20 wt% glutaraldehyde aqueous solution II for 24 hours, and then the product III is taken out after soaking, and the excess glutaraldehyde in the glutaraldehyde aqueous solution II is removed by water, and then dried at 25° C. for 72 hours to obtain a thermal insulation and breathable fiber; wherein the mass volume ratio of the product III to the glutaraldehyde aqueous solution II is 1:4.

[0084] The moisture permeability of the cloth made of the above-prepared warm breathable fiber at 20°C is 6205g·(m 2 24h) -1 The change rate of moisture permeability after washing at 20°C is 2.4%, and the moisture permeability at 30°C is 7550g·(m 2 24h) -1 The change rate of moisture permeability after washing at 30°C is 2.1%, and the moisture permeability at 40°C is 8853g·(m 2 24h) -1 The change rate of moisture permeability after washing at 40°C is 2.4%.

Claims

1. A method for preparing a thermal-retaining breathable fiber, characterized in that: The flax fiber or cellulose fiber is immersed in a glutaraldehyde aqueous solution I to obtain a product I, and then the product I is taken out and immersed in polyethylene glycol in a molten state to obtain a product II, and then the product II is taken out and immersed in a polyphenol aqueous solution and a metal ion aqueous solution is added to the polyphenol aqueous solution to perform self-assembly of a metal polyphenol network to obtain a product III, and finally the product III is taken out and immersed in a glutaraldehyde aqueous solution II to react to obtain a final product, i.e., a thermal insulation breathable fiber; The metal polyphenol network is obtained by the coordination of metal ions and polyphenols; In the solution obtained by adding the metal ion aqueous solution to the polyphenol aqueous solution, the molar amount of the metal ions is greater than the molar amount of the polyphenols.

2. The method for preparing a thermal-insulating and breathable fiber according to claim 1, characterized in that: The specific preparation steps are: (1) Soaking flax fiber or cellulose fiber in a 30-50 wt% glutaraldehyde aqueous solution I for 6-24 hours; the temperature of the glutaraldehyde aqueous solution I is 25-45° C.; (2) placing the product soaked in step (1) in molten polyethylene glycol for 0.5 to 2 hours, and then vacuum drying at 40 to 60° C. for 4 to 8 hours; (3) placing the vacuum-dried product of step (2) in a polyphenol aqueous solution with a concentration of 1 to 10 wt% for 10 to 30 minutes, then pouring a 10 to 25° C. metal ion aqueous solution into the polyphenol aqueous solution and allowing the mixture to stand for 2 to 8 hours, and finally drying the product at 25 to 60° C. for 20 to 40 minutes; (4) The dried product of step (3) is placed in a 10-30 wt% glutaraldehyde aqueous solution II for 6-24 hours to obtain a thermal insulation and breathable fiber.

3. The method for preparing a thermal-retaining breathable fiber according to claim 2, characterized in that: The mass volume ratio of the flax fiber or cellulose fiber to the glutaraldehyde aqueous solution I is 1:10-50.

4. The method for preparing a thermal-insulating and breathable fiber according to claim 2, characterized in that: The mass volume ratio of the product after immersion in step (1) to the molten polyethylene glycol is 1:10-30; the mass volume ratio of the product after vacuum drying in step (2) to the polyphenol aqueous solution is 1:5-25; and the mass volume ratio of the product after drying in step (3) to the glutaraldehyde aqueous solution II is 1:4-20.

5. The method for preparing a thermal-retaining breathable fiber according to claim 1, characterized in that: The molar ratio of polyphenols to metal ions is 1:2~10.

6. The method for preparing a thermal-retaining breathable fiber according to claim 5, characterized in that: The metal ions are one or more selected from the group consisting of copper ions, zinc ions, zirconium ions, iron ions and ferrous ions; the polyphenols are one or more selected from the group consisting of tannic acid, gallic acid, catechol and pyrogallol; and the polyethylene glycol is one or more selected from the group consisting of polyethylene glycol 1000, polyethylene glycol 2000, polyethylene glycol 4000, polyethylene glycol 6000 and polyethylene glycol 10000.

7. The method for preparing a thermal-insulating and breathable fiber according to claim 1, characterized in that: The moisture permeability of the cloth made of thermal breathable fiber at 20℃ is 6174~6278g·(m 2 24h) -1 The change rate of moisture permeability after washing at 20℃ is 1.3~3.7%, and the moisture permeability at 30℃ is 7492~7597g·(m 2 24h) -1 The change rate of moisture permeability after washing at 30℃ is 1.7~3%, and the moisture permeability at 40℃ is 8795~8906g·(m 2 24h) -1 The change rate of moisture permeability after washing at 40°C is 1.9~3%.

Citation Information

Patent Citations

  • Bone repair material containing metal-phenolic network, and preparation method and application thereof

    CN113769166A

  • Cannabidiol finishing liquid and finishing process of cannabidiol functional fabric

    CN113818240A

  • Method for making catechins waterproof

    JP2007186833A

  • English name conversion service providing server that provides the english conversion service for korean name and the operating method thereof

    KR102924037B1

  • Fiber-treating agent

    US20240060234A1